Habitat preferences and seasonality of bird species of Pantanos de Villa in Lima, Peru - Pulido, Víctor (2020)
In the wildlife refuge Pantanos de Villa, habitat preferences of resident and migratory birds were analyzed according to the seasonality of 211 species of birds, of which 97 were residents, 82 migratories and 32 occasional visitors. According to use of habitats: 80.1% of species live on any of these wetlands, 40.8% in the marine coast, 37.9% in parks and gardens, 33.2% in wetlands and the beach, 34.1% in wetlands and parks and gardens and 1.0% in marine sandy beach and parks and gardens. Higher species similarity was between those living in “shrubland zones” and “parks and gardens” (82.3%). Fluctuation intensity of the species richness varied according to their occupance habitats, with the highest value observed between March and May in the water bodies (25) and marine coast (24). Management of the Pantanos de Villa must prioritize maintenance of heterogeneity of habitats because the low similarity degree would show species exclusivity of each of them. Comparisons between preferences of habitats of birds and plants would demonstrate the need of consider more than one taxa in decision-making for the management and conservation of biodiversity of coastal wetlands.